Man-of-war - Platt, Richard (Biesty, Stephen. Cross-sections., 2019)
Presents a visual tour via cross-section illustrations of a British Man-of-War naval ship from Great Britain's royal Navy as it might have looked in about the year 1800. Covers the different decks and compartment of the ship, the roles of each sailor and officer, the struggles of life at sea, how sailors stayed healthy--or did not--and how naval battles were conducted at that time. Includes a glossary.